Dicyclohexylammonium thiocyanate - Khawar Rauf, M. (International Union of Crystallography, 2008)
In the crystal structure of the title compound, C(12)H(24)N(+)·NCS(−), the anions and cations are linked through N—H⋯N and N—H⋯S hydrogen bonds, resulting in a chain along the a axis.